Social Capital Influence Towards Sustainability of Herbal Medicine Trade In Nguter Market Sukoharjo - Rismaningtyas, Fitria; Slamet, Yulius; Haryono, Bagus (Advances in Social Sciences Research Journal, 2018)
ABSTRACT The aim of this research is to analyze total direct influence of trust and networks towards sustainability of herbal medicine trade in Nguter market Sukoharjo. This research begun at February, 2018. Data collection through observation and questionnaire towards herbal medicine trader in Nguter market. The data analysis done by description and path analysis. The data processing using SPSS 21 Software as analysis tool. The result show that there’s direct influence of trust variable towards the sustainbility of herbal medicine trade, 0.378 or 14.2%. Meanwhile direct influence of networks variable towards the sustainbility of herbal medicine trade, 0.374 or 12.1%. Trust variable has bigger contribution than network variable, 14.2%>12.1%. This number shows the importance of trust among herbal medicine traders, market administrator, herbal medicine’s fund managment agency, and the herbal medicine customers. Trust variable has big role on sustainbility of herbal medicine trade, there’s desire and needs to maintain the trust among the related actors. Keywords: social capital, networks, trust, sustainability trade, herbal medicine traders.